Nitriding‐Interface‐Regulated Lithium Plating Enables Flame‐Retardant Electrolytes for High‐Voltage Lithium Metal Batteries - Tan, Shuang‐Jie; Yue, Junpei; Hu, Xin‐Cheng; Shen, Zhen‐Zhen; Wang, Wen‐Peng; Li, Jin‐Yi; Zuo, Tong‐Tong; Duan, Hui; Xiao, Yao; Yin, Ya‐Xia; Wen, Rui; Guo, Yu‐Guo (Angewandte Chemie International Edition, 2019)
Safety concerns are impeding the applications of lithium metal batteries. Flame‐retardant electrolytes, such as organic phosphates electrolytes (OPEs), could intrinsically eliminate fire hazards and improve battery safety. However, OPEs show poor compatibility with Li metal though the exact reason has yet to be identified. Here, the lithium plating process in OPEs and Li/OPEs interface chemistry were investigated through ex situ and in situ techniques, and the cause for this incompatibility was revealed to be the highly resistive and inhomogeneous interfaces. Further, a nitriding interface strategy was proposed to ameliorate this issue and a Li metal anode with an improved Li cycling stability (300 h) and dendrite‐free morphology is achieved. Meanwhile, the full batteries coupled with nickel‐rich cathodes, such as LiNi0.8Co0.1Mn0.1O2, show excellent cycling stability and outstanding safety (passed the nail penetration test). This successful nitriding‐interface strategy paves a new way to handle the incompatibility between electrode and electrolyte. A nitriding interface has been developed for the successful application of flame‐retardant electrolytes in high‐energy‐density cells using a Li metal anode and a high‐voltage, high‐capacity cathode. The homogeneity of the solid electrolyte interface (SEI) layer is crucially important for the uniform Li deposition required for high‐voltage batteries.